2011
DOI: 10.1590/s1516-35982011000900018
|View full text |Cite
|
Sign up to set email alerts
|

Níveis de energia líquida e ractopamina para leitoas em terminação sob conforto térmico

Abstract: RESUMO -Objetivou-se com este estudo avaliar níveis de energia líquida e ractopamina em dietas para leitoas em terminação sob conforto térmico. Foram utilizadas 40 leitoas com peso inicial de 67,4 ± 3,4 kg, distribuídas em delineamento de blocos ao acaso em esquema fatorial 2 × 4, composto de dois níveis de ractopamina, 0 e 20 ppm, em combinação aos níveis de energia líquida de 2.300; 2.424; 2.548 e 2.668 kcal/kg de ração, com cinco repetições, considerando cada animal uma unidade experimental. O período exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
(31 reference statements)
0
6
1
Order By: Relevance
“…Contrary to the fi ndings of MOURA et al (2011), who reported no effect of NE content on ADG of 60-to 90-kg gilts, the results of our studies indicate that dietary NE content may affect the performance of pigs fed low-CP diets supplemented with industrial amino acids by favoring a higher DL and NE intakes, possibly due to the lower thermogenic effect of these type of diets. It also must be considered that the greater ADG of pigs fed the diets containing 155g kg -1 CP and 2566kcal kg -1 NE (Exp.…”
Section: ----------------------------------Crude Protein (G Kg -1 ) Acontrasting
confidence: 99%
See 2 more Smart Citations
“…Contrary to the fi ndings of MOURA et al (2011), who reported no effect of NE content on ADG of 60-to 90-kg gilts, the results of our studies indicate that dietary NE content may affect the performance of pigs fed low-CP diets supplemented with industrial amino acids by favoring a higher DL and NE intakes, possibly due to the lower thermogenic effect of these type of diets. It also must be considered that the greater ADG of pigs fed the diets containing 155g kg -1 CP and 2566kcal kg -1 NE (Exp.…”
Section: ----------------------------------Crude Protein (G Kg -1 ) Acontrasting
confidence: 99%
“…Similarly, VIDAL et al (2010) Ciência Rural, v.44, n.9, set, 2014. reduced 45g kg -1 CP in the diet for 70-to 100-kg pigs without any variation on ADFI. In a more recent study, MOURA et al (2011) evaluated NE in diets for fi nishing gilts (60-to 92-kg) and also verifi ed no effect on ADFI.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Similarly, VIDAL et al (2010) Ciência Rural, v.44, n.9, set, 2014. reduced 45g kg -1 CP in the diet for 70-to 100-kg pigs without any variation on ADFI. In a more recent study, MOURA et al (2011) evaluated NE in diets for fi nishing gilts (60-to 92-kg) and also verifi ed no effect on ADFI.…”
Section: Resultsmentioning
confidence: 98%
“…REZENDE et al (2006) evaluating levels of energy for fi nishing barrows with energy concentrations been obtained by including soybean oil in the diets which probably contributed to increase dietary NE content (NOBLET & SHI, 1994), also found no effect on carcass traits. More recently, MOURA et al (2011), investigating the effects of increased NE levels (2300 to 2668kcal kg -1 ) in diets for fi nishing gilts observed no differences on lean meat percentage and carcass yield. PAIANO et - al.…”
Section: ---------------------------------Crude Protein (G Kg -1 ) Anmentioning
confidence: 99%